Molecularly Imprinted Poly(Methyl Red) Modified Carbon Paste Electrode for Voltammetric Determination of Paracetamol - Nurdiani, Witri
Paracetamol is used as antypyretic and analgesic drug. However, overdoses of paracetamol can affect metabolism and cause hepatotoxicity and nephrotoxicity. Therefore, accurate paracetamol determination method is required. In this research, we developed a voltammetry method for paracetamol determination using carbon paste electrode (CPE) modified with molecularly imprinted poly(methyl red) as working electrode. Carbon paste electrode was modified through electropolymerization of methyl red from solution containing mixture of methyl red and paracetamol in phosphate buffer solution (pH 7). The electropolymerizatio was conducted using cyclic voltammetry technique in potential range of -1,0 V – 1,4 V at a scan rate of 100 mVs-1 for 10 cycles. Paracetamol measurement was carried out with differential pulse voltammetry technique in potential range of 0,2 V – 0,8 V at a scan rate of 10 mVs-1. Linear calibration curve was obtained in the concentration range of 0,01 mM – 0,1 mM with a detection limit of 3,0 ?M. Peak current obtained from 20 repeated measurements showed a relative standard deviation of 3,7%. Determination of paracetamol in commercial drug samples showed good accuration with a % recovery of 99,6 - 104,9%.